Vanillin Promotes the Germination of Antrodia camphorata Arthroconidia through PKA and MAPK Signaling Pathways - Lu, Zhen-Ming; Zhu, Qing; Li, Hua-Xiang; Geng, Yan; Shi, Jin-Song; Xu, Zheng-Hong (Frontiers in Microbiology, 2017)
Wild fruiting bodies of medicinal mushroom Antrodia camphorata are only found on the endemic species bull camphor tree, Cinnamomum kanehirae, in Taiwan. Despite the evident importance of the host components in promoting the growth of A. camphorata, insights into the underlying mechanisms are still lacking. Here, we first evaluated effects of the compounds from C. kanehirai, C. camphora, and A. camphorata, and their structural analogues on the germination rate of A. camphorata arthroconidia. Among the 54 tested compounds, vanillin (4-hydroxy-3-methoxybenzaldehyde) was determined as the optimum germination promoter, while o-vanillin and 1-octen-3-ol as major negative regulators of arthroconidia germination. Second, the protein patterns of arthroconidia after 24 h of incubation in the presence or absence of vanillin were compared via isobaric tags for relative and absolute quantitation (iTRAQ)-based proteomics. Via bioinformatic analysis, it was found that 61 proteins might relate to the germination of arthroconidia, in which 16 proteins might involve in two potential protein kinase A (PKA) and mitogen-activated protein kinase (MAPK) signaling pathways in the vanillin-promoted germination of A. camphorata arthroconidia. Last, the mRNA expression levels of the 16 germination-related genes in the potential PKA and MAPK signaling pathways were analyzed by quantitative real time PCR. Together, our results are beneficial for the elucidation of molecular mechanisms underlying the germination of A. camphorata arthroconidia.